RANCANG BANGUN REAKTOR BIOGAS SKALA RUMAH TANGGA - Basri, Abdul Khasman; Kadirman, Kadirman; Jamaluddin, Jamaluddin (Universitas Negeri Makassar, 2019)
Inadequate disposal of livestock manure has caused environmental pollution around the village, both water, soil and air (smell). Animal waste in the form of liquid is deliberately flowed into the river while solid waste is left piled up around the cage. The occurrence of odor and pollution is sometimes triggered social conflict, with complaints from local communities. With a population of 35 head of cattle for a farmer group, assuming the average per cow yields 15 kg of solid waste, the waste produced can reach approximately 525 kg per day. The lack of knowledge and the low educational background of the cattle ranchers in the Arabica Village makes the awareness of the environment to be lacking, as well as the technology of processing animal waste and the benefits. Biogas Reaktors of animal waste, although they have heard but lack of knowledge of how to make biogas installations and the assumption that the budget is spent to build the technology makes them prefer to allocate these funds to other things in order for the survival of livestock business can be sustainable. By looking at the existing potential, of course, if managed properly, Arabica Village can become an energy independent village and is a new business opportunity, for biogas products and residues from the installation of biogas in the form of organic fertilizer.